Implications of some types of pairwise closed graphs - Bouseliana, Hend; Kilicman, Adem (Universidad Catolica del Norte Antofagasta, 2022)
The main goal of this paper is to introduce and look into some of the fundamental properties of pairwise strongly closed, pairwise strongly -closed and pairwise quasi -closed graphs. Some characterizations and several properties concerning these graphs are obtained. We also investigate relationships between (i,j)-strongly alpha -closed graph G(f) and (i,j)-weakly alpha -continuous. We study relationships between (i,j) strongly alpha -closed (i,j)-quasi alpha-closed graphs with covering properties. The concepts of pairwise -closed and pairwise quasi H-closed relatively are stated.